2022
DOI: 10.3389/fphy.2022.860419
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Oscillations of Surface Tension Induced by an A + B → C Traveling Front

Abstract: This work describes a new mechanism for the emergence of oscillatory dynamics driven by the interaction of hydrodynamic flows and reaction-diffusion processes with no autocatalytic feedback nor prescribed hydrodynamic instability involved. To do so, we study the dynamics of an A+ B → C reaction-diffusion front in the presence of chemically-driven Marangoni flows for arbitrary initial concentrations of reactants and diffusion coefficients of all species. All the species are assumed to affect the solution surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As a natural extension of this work, we could investigate differential diffusion effects on the system dynamics, starting with the case a0Da=b0Db, where the RD front is stationary, since it is naturally more common in experiments that species diffuse at different rates. On the basis of the recent findings that differential diffusion effects coupled with Marangoni stresses can trigger spatio-temporal oscillations of surface tension along with a discontinuous motion of the front along the free surface [13], we expect much more exotic possibilities for the dynamical properties of the reaction front when all the species diffuse at different rates. Along the same line, the effects of reaction exothermicity in both cases of cooperative and competitive solutal and thermal effects and the coupling to buoyancy-driven convection for unequal initial reactants concentrations and/or differential diffusion effects could be envisioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a natural extension of this work, we could investigate differential diffusion effects on the system dynamics, starting with the case a0Da=b0Db, where the RD front is stationary, since it is naturally more common in experiments that species diffuse at different rates. On the basis of the recent findings that differential diffusion effects coupled with Marangoni stresses can trigger spatio-temporal oscillations of surface tension along with a discontinuous motion of the front along the free surface [13], we expect much more exotic possibilities for the dynamical properties of the reaction front when all the species diffuse at different rates. Along the same line, the effects of reaction exothermicity in both cases of cooperative and competitive solutal and thermal effects and the coupling to buoyancy-driven convection for unequal initial reactants concentrations and/or differential diffusion effects could be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…When the surface tension changes during the reaction are large enough, transient oscillations can also be observed in the presence of Marangoni-driven convection, while sustained oscillations are noted when combined with buoyant forces [10][11][12]. Recently, as a unique feature of differential diffusion effects coupled with Marangoni stresses, transient spatio-temporal oscillations of surface tension along with a discontinuous motion of the front have been shown to emerge for appropriate conditions on the model parameters, the mechanism of which does not require any autocatalytic feedback nor prescribed hydrodynamic instability [13].…”
Section: Introductionmentioning
confidence: 99%
“…25 When those fronts are studied in aqueous media, convective flows can be triggered if the reaction induces changes in density (Δ R ≠ 0) or in surface tension (Δ M ≠ 0). The pure buoyancy- 60 and Marangoni- 61 driven convective cases have shown propagating fronts, and transient oscillatory dynamics have been reported in the latter case for both equal 30 and differential 33 molecular diffusion coefficients.…”
Section: Chemo-marangoni-buoyancy Oscillationsmentioning
confidence: 92%
“…29 It was recently shown that simple A + B -C reactions can also exhibit spatiotemporal oscillations, provided that the reaction combines with hydrodynamics. [30][31][32][33] In reactive fluids, natural convection can indeed arise spontaneously from changes in the composition/temperature of the system, further inducing in situ local gradients in the physical properties (i.e. density and/or surface tension), thereby activating convective motions within the fluid itself.…”
Section: Introductionmentioning
confidence: 99%